Daya Terima Sosis Substitusi Tahu dan Tepung Kacang lentil Merah sebagai Selingan Remaja Putri Overweight - Khansa Nur Fauzia; Annis Catur Adi (Yayasan Literasi Sains Indonesia, 2026)
Adolescent overweight is associated with high-fat and low-fiber dietary patterns, including the consumption of processed foods such as sausages. This study aimed to analyze the effect of tofu and red lentil flour substitution in chicken sausage on sensory acceptability and nutritional content as an alternative snack for overweight adolescent girls. This quantitative experimental study employed a Completely Randomized Design (CRD) with three tested formulations: F0 (control), F1 (45%), and F2 (60%). Hedonic tests were conducted by 30 untrained panelists evaluating color, aroma, taste, and texture using a 5-point Likert scale. Data were analyzed using the Shapiro–Wilk test, Friedman test, and Wilcoxon signed-rank test. The results showed significant differences in color (p=0.030), taste (p=0.000), and texture (p=0.000), but not in aroma (p=0.104). F2 obtained the highest scores for color (4.30) and aroma (4.53), while F0 scored highest for taste (4.43) and texture (4.23). Nutritional analysis indicated that increasing the level of substitution increased fiber content from 0.58 g to 4.40 g per serving and reduced fat content from 6.39 g to 5.45 g per serving. This study concludes that tofu and red lentil flour substitution affects the sensory acceptability of chicken sausage and has the potential to produce a high-fiber, low-fat snack alternative for overweight adolescent girls.